Implementasi Metode Vector Space Model pada Search Engine Perpustakaan - Stevanus Salmon; Debby Paseru; Vivie Kumenap (Ikatan Ahli Informatika Indonesia, 2020)
Dinas Perpustakaan dan Kearsipan Daerah Provinsi Sulawesi Utara is a library owned by the provincial government of Sulawesi Utara (Sulut), which provides various sources of information needed by the community such as books or reference documents. Other. This library provides various facilities and services that can be used by the community of Sulut such as searching, reading and borrowing books. Libraries are required to be able to improve their services especially in book Search or documents. The book search process in a library that requires visitors to visit each of the booksets will take a long time. In addition, visitors should also first find the fields or topics of the searched book by visiting the Bookcloset section that corresponds to the field or topic. The lack of information available about books or documents in the library will prevent visitors from finding the information they need. Therefore the library requires a system to simplify the process of searching the book. A book search system that uses the search process by matching keywords and data to the database, will only display the title of the book exactly as the keyword entered on the search form. If the user forgets the details of the title of the book to be searched, it is very difficult to search the book title because the system is unable to display the corresponding title of the book or is relevant to the book title entered on the search form. To be able to display the information or title of the book related or relevant to the title of the book to be searched, will be created a search system of books that use an information retrieval system or the information Retrieval (IR). Information Retrieval (IR) or an info-back system is one way to easily rediscover the information on documents contained in a system. Search engine or search engine is a device that can facilitate the user to obtain information by displaying the search results according to the information that is sought by the user. On this final task will be built search engine libraries that can make it easier for users to rediscover relevant books according to the data sought. This final task applies a Vector Space Model (VSM) method that is one of several methods that can be used in building the System Information Retrieval (IR). The result of this final task is a search engine library by implementing a VSM method that provides the document search feature and provides a complete document or book information in the library. In addition, testing of the application uses recall and precision which results in a value of 1 which shows that the system can find the relevant documents according to the relevant documents in the collection.